1997
DOI: 10.1113/expphysiol.1997.sp004073
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms responsible for changes in abdominal vascular volume during sympathetic nerve stimulation in anaesthetized dogs

Abstract: SUMMARYThis study was designed to determine the extent to which the decrease in volume of blood in the abdominal circulation in response to sympathetic stimulation was due to a passive effect of decreasing flow rather than an active constriction of the capacitance vessels. In dogs anaesthetized with a-chloralose (100 mg kg-' I.v.) the abdominal circulation was vascularly isolated and perfused either at constant flow or at constant pressure, and drained at constant pressure from the inferior vena cava. Changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
0
14
1
Order By: Relevance
“…This is based partly on observing that responses in that region, induced by either direct or reflex stimulation of sympathetic nerves (e.g. Noble et al 1997), were not very different from changes observed by others in the whole body (Shoukas & Sagawa, 1973;Brunner et al 1981). Also, studies of responses in other regions, particularly the limb circulation (Hainsworth et al 1983) or in perfused muscle (Lesh & Rothe, 1969), have shown that these regions do not show significant changes in volume in response to stimulation, provided that flow does not change and thereby cause secondary passive changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is based partly on observing that responses in that region, induced by either direct or reflex stimulation of sympathetic nerves (e.g. Noble et al 1997), were not very different from changes observed by others in the whole body (Shoukas & Sagawa, 1973;Brunner et al 1981). Also, studies of responses in other regions, particularly the limb circulation (Hainsworth et al 1983) or in perfused muscle (Lesh & Rothe, 1969), have shown that these regions do not show significant changes in volume in response to stimulation, provided that flow does not change and thereby cause secondary passive changes.…”
Section: Discussionmentioning
confidence: 99%
“…This passive effect also occurs in the abdominal circulation and is much larger there, attributable to the high vascular compliance of that region . In fact, comparisons of responses during constant pressure and constant flow perfusion (Brooksby & Donald, 1972;Noble et al 1997) have shown that the passive volume changes occurring secondarily to changes in flow are of a similar magnitude to the active capacitance effects. Previous investigations have established that, in the dog, the spleen makes a large contribution to the active response, but very little to the passive change (Noble et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, not only does the abdominal circulation make the major contribution to capacitance control (Karim & Hainsworth, 1976;Noble et al 1997) but its high compliance, at about 9.25 ml kg-' kPa-', accounts for about half the entire vascular compliance of the whole body (Echt, Lange & Gauer, 1974;Drees & Rothe, 1974;Larochelle & Ogilvie, 1976). In the dog, a large contribution to the active response is from the spleen (Greenway, Lawson & Stark, 1968;Donald & Aarhus, 1974;Noble et al 1997). Since humans do not possess a large contractile spleen, any extrapolation of results from dogs to humans should take account of the fact that the canine spleen contributes 40 % or more of the active volume change.…”
Section: Discussionmentioning
confidence: 99%
“…However, results obtained cannot be extrapolated quantitatively to humans because in the dog a major contribution to capacitance is from the spleen which, in that species and unlike humans, is very large and contractile. Indeed, in the dog, changes in splenic blood volume can account for up to half the total volume response to sympathetic stimulation (Karim & Hainsworth, 1976;Carneiro & Donald, 1977;Noble, Drinkhill, Myers & Hainsworth, 1997). The liver is the other large organ in the abdomen and previous work has indicated that its vascular volume can change in response to various interventions, including efferent sympathetic nerve stimulation and haemorrhage (Greenway, Stark & Lautt, 1969;Carneiro & Donald, 1977;Greenway, Innes & Scott, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Active constriction of the splanchnic capacitance vessels is potentially of great importance in mobilizing additional venous blood to maintain the cardiac filling pressures and, hence, stroke volume during orthostatic stress. In dogs, baroreflex-mediated active venoconstriction occurs in the venous beds of the liver and spleen in particular (Karim & Hainsworth, 1976;Noble et al 1997Noble et al , 1998. The rich innervation and the great sensitivity and rapidity of the reflex responses of the splanchnic capacitance vessels to very low frequencies of sympathetic discharge are supportive of their importance in responding to postural changes (Shepherd, 1986;Hainsworth, 1990).…”
Section: Splanchnic the Splanchnic Vascular Bed Is Richly Innervatedmentioning
confidence: 99%